The History PF Training Intellectual Personnel in Uzbekistan and Reforms Implemented in This Field (Open Herald: Periodical of Methodical Research, 2024)
This article discusses the history of training intellectuals in Central Asia, particularly in Uzbekistan, and the reforms implemented in the field of training intellectual personnel in Uzbekistan. It highlights the essence of these reforms and the processes of reforms based on the demands of the times and society as outlined in normative legal acts.